Identification and elimination of false-positives in an ELISA-based system for qualitative assessment of glycoconjugate binding using a selection of plant lectins - Babak Afrough; Miriam V. Dwek; Pamela Greenwell (BioTechniques, 2007)
Systematic optimization of a lectin-based enzyme-linked immunosorbent assay (ELISA) procedure using a panel of 21 biotinylated plant lectins and a glycoprotein with defined glycosylation (i) identified blocking as a limiting step in solid phase sugar binding analysis and (ii) found Synblock to be a better alternative to bovine serum albumin (BSA) as blocking agent.